Uterus transplantation: An innovative perspective (Research, Society and Development, 2022)
Uterine transplantation has been analyzed for admission to regulated transplants in Brazil, since uterine involvement is an important cause of morbidity worldwide, being responsible for affecting family harmony by becoming a major obstacle to the generation of a child. Therefore, there are occurrences of uterine malformations that cannot be corrected through surgery, in addition to infertility due to the absence of the uterus, which are determining factors for the indication of uterus transplantation. This surgical procedure is a new technique used especially in patients diagnosed with total infertility of uterine reason, in which the vigorous uterus is donated to a woman affected by Uterine Infertility Factor, as well as women under the age of 44 who have already undergone surgery to remove the uterus, giving good chances if the desire to become pregnant persists. Thus, uterine transplantation is characterized as a complex procedure, which can entail risks for the donor and recipient in the postoperative period, but which also has high success rates, as around 50 uterus transplants have been performed worldwide. performed, and of these, 16 transplants had good results.